Marathon performance but not BMI affects post-marathon pro-inflammatory and cartilage biomarkers - Mündermann, A.; Geurts, J.; Hügle, T.; Nickel, T.; Schmidt-Trucksäss, A.; Halle, M.; Hanssen, H. (Journal of Sports Sciences, 2017)
We tested the hypothesis that changes in serum cartilage oligomeric matrix protein (COMP), tumour necrosis factor a (TNF-a), interleukin-6 (IL-6) and high-sensitivity C-reactive protein (hsCRP) concentration after regular endurance training and running a marathon race depend on body mass index (BMI) and/or on marathon performance. Blood samples were collected from 45 runners of varying BMI and running experience before and after a 10-week marathon training programme and before, immediately and 24 h after a marathon race. Serum biomarker concentrations, BMI and marathon finishing time were measured. The mean (95% confidence interval (CI)) changes from before to immediately after the marathon were COMP: 4.09 U/L (3.39-4.79 U/L); TNF-a: -1.17 mg/L (-2.58 to 0.25 mg/L); IL-6: 12.0 pg/mL (11.4-12.5 pg/mL); and hsCRP: -0.08 pg/mL (-0.14 to -0.3 pg/mL). The mean (95% CI) changes from immediately after to 24 h after the marathon were COMP: 0.35 U/L (-0.88 to 1.57 U/L); TNF-a: -0.43 mg/L (-0.99 to 0.13 mg/L); IL-6: -9.9 pg/mL (-10.5 to -9.4 pg/mL); and hsCRP: 1.52 pg/mL (1.25-1.79 pg/mL). BMI did not affect changes in biomarker concentrations. Differences in marathon finishing time explained 32% of variability in changes in serum hsCRP and 28% of variability in changes in serum COMP during the 24 h recovery after the marathon race (P < 0.001). Slower marathon finishing time but not a higher BMI modulates increases in pro-inflammatory markers or cartilage markers following a marathon race.